Correlation of Scale Factor Non-Linearity and Vibration Rectification Error in Vibrating Beam Accelerometers - Theo Miani; Lokesh Gurung; Douglas Young; Madan Parajuli; Guillermo Sobreviela-Falces; Colin Baker; Ashwin A. Seshia (IEEE Access)
Vibration Rectification Error (VRE) is a critical parameter for high-performance accelerometers operating in dynamic environments. This paper presents a focused experimental study to rigorously investigate the relationship between VRE and Scale Factor Non-Linearity (SFNL) in vibrating beam MEMS accelerometers (VBAs). A robust experimental setup is developed to suppress external influences and measurement errors, ensuring that the observed VRE originates solely from intrinsic sensor behavior. By refining the measurement methodology and isolating SFNL contributions, this work establishes a clear and quantitative link between quadratic term of SFNL and VRE. After limiting the VRE contribution to the mechanical behavior of the MEMS, the understanding of amplification phenomenon allow explaining the bandwidth dependency. The results demonstrate that the dominant source of VRE is the 2nd-order term of SFNL, confirming the effectiveness of low-bias VBAs in mitigating 2nd-order SFNL, thereby reducing VRE. These findings define a robust framework for accurate VRE characterization and provide the foundation for advanced VRE reduction strategies.